Optimalisasi FoMO dalam Copywriting PAS dengan Pemanfaatan Cinta Tanah Air - Rolan Mart Sasongko; Rifky Adiyatna, Hafidh; Saraswati, Yudhistira (Jurnal Kabar Masyarakat, 2023)
This research discusses the training of copywriting training and its impact on increasing sales of MSME products in Yogyakarta City. Yogyakarta. This training aims to improve participants' skills in producing effective copywriting that attracts consumers' attention. The training method involved the delivery of materials by the instructor on the importance of copywriting, techniques for creating attractive copywriting, and strategies to utilize the to utilize the "I Love Indonesian Products" tagline. Results training showed that participants were able to identify specific problems faced by consumers and offer solutions through their products using compelling copywriting. using compelling copywriting. With the use of strong taglines, such as "I Love Indonesian Products", participants were able to design copywriting copywriting sentences that attract attention and arouse curiosity in consumers. curiosity of consumers. This training has a positive impact on increasing branding and sales of MSME products in Yogyakarta City.